Voltammetric immunoassay for the human blood clotting factor IX by using nanogapped dielectrode junctions modified with gold nanoparticle-conjugated antibody - Gopinath, S.C.B. (Springer-Verlag Wien, 2017)
The authors describe an electrochemical method for the determination of the blood clotting factor IX (FIX). A nanogapped dielectrode (with a < 100 nm junction) was modified with antibody against FIX, and the resulting system was characterized by both impedance spectroscopy and voltammetry. In order to attain the improved sensitivity, gold nanoparticles were electrostatically attached to FIX. The current to voltage (I-V) measurement was carried out from 1 V to 5 V, where the entire calibration plot with 5 V was taken. This results in a limit of detection as low of 1 pM, which is much lower compared to the real concentration of FIX (87 nM) in human blood serum. The analytical range extends from 1 pM to 0.1 μM. The electrode is highly specific over other serum proteins. © 2017, Springer-Verlag GmbH Austria.